Application of Fintech Financial Technology in the Stock Market in Vietnam - Nga, Nguyen Thi Thuy (Business and Economic Research, 2024)
Along with the strong development of science and technology, the application of modern technology in many activities in the financial market, including the stock market, has contributed to promoting and creating new steps. a major turning point in the development and integration of these markets. The application of modern technology has created technological leaps in the financial sector around the world, bringing incredible changes in the fields of securities, banking, and investment. Currently, Fintech is playing an important role in changing the way investors participate in the stock market. The profound impact of the 4.0 Industrial Revolution is and has been taking place strongly on most industries around the world in general and Vietnam in particular, so the stock market is no exception to that trend. Developing the stock market towards integrating modern information technology applications is an inevitable trend. Recognizing the importance of information technology application in the field of securities and stock market, the State Securities Commission has gradually modernized the technology platform to improve management and supervision capacity, operating and serving the development of the market. Regarding the development of securities products and services, since 2017, a number of securities companies have researched and deployed financial technology applications to increase customers' investment experience. Up to now, Fintech has helped new investors easily access stock investment channels with many convenient trading features, low costs, saving time and effort. However, Fintech applications in stock trading in our country are not really diverse, still at a simple level such as supporting buying and selling transactions, providing transaction information for investors. The article provides comments and assessments on the current status of Fintech applications in stock trading in Vietnam and some proposals to widely deploy these applications in the stock market in the near future.